2018
DOI: 10.1111/jen.12567
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in natural mortality factors of Tuta absoluta (Lepidoptera: Gelechiidae) in open‐field tomato cultivation

Abstract: The seasonal variation in natural mortality of phytophagous insects is determined by the relative importance of biotic and abiotic factors in agroecosystems. Knowledge regarding these factors throughout the year represents a key concern for IPM programmes. Seasonal population fluctuations of tomato pinworm, Tuta absoluta, led to an investigation of its natural mortality factors during the rainy season when the population level is low and during the dry season when population peaks occur. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
0
14
0
3
Order By: Relevance
“…The demand for more sustainable pest control measures is being driven by the ever increasing levels of insecticide resistance now observed in many pest populations and concerns for environmental safety (Silva et al 2011;Bacci et al 2019). The use of biological control is an alternative to synthetic insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…The demand for more sustainable pest control measures is being driven by the ever increasing levels of insecticide resistance now observed in many pest populations and concerns for environmental safety (Silva et al 2011;Bacci et al 2019). The use of biological control is an alternative to synthetic insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Some pheromone traps caught about 40% more insects in summer 2018 than in spring 2019 (data not shown). Seasonal variations in the surrounding agroecosystem (the landscape) and climatic conditions could affect the role and effectiveness of naturally occurring biocontrol agents, demographic parameters of T. absoluta, plant physiology, and consequently the abundance of the pest and the intensity of the attack (Bacci et al, 2019). No significant difference in mean temperatures was recorded between summer 2018 and spring 2019 (28-30°C, very close to the optimum for T. absoluta development); therefore, the low relative humidity and precipitation during the 2019 trial and throughout that year may have led to higher mortality rates and/or lower rates of development of T. absoluta, and/or may have affected the availability and quality of resources (Guimapi et al, 2016).…”
Section: Infestation Of Untreated Field-grown Tomatoes: Rate and Variability Of Damagementioning
confidence: 99%
“…The species was successfully used in Brazil to control Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in tomato fields (Haji et al 2002) and has stimulated research in several crops to control other lepidopteran species (Parra & Zucchi 2004). In fact, T. pretiosum was considered an important mortality factor of T. absoluta eggs in conventional (Bacci et al 2018) and organic tomato fields (Medeiros et al 2011). Moreover, Figueiredo et al (2015) demonstrated that the release of T. pretiosum to control S. frugiperda eggs in organic maize increased maize productivity by 19.4% in Brazil. Among the predators, the number of products per species is more balanced than the other BCAs, with five species of predators being associated with 10 different products (Table 1).…”
Section: Arthropod Control Agentsmentioning
confidence: 99%